Gastrointestinal taste receptors: could tastants become drugs?. Issue 2 (April 2020) - Behrens, Maik; Somoza, Veronika
Abstract : Purpose of review: Numerous studies have pointed to profound nongustatory roles of tastants and the corresponding taste receptors expressed in the alimentary canal in the modulation of digestive and metabolic functions. Already in early reports, the intriguing possibility to use tastants as drug-like effectors for the treatment of metabolic diseases was raised. With this review, focusing on the most recent literature, we intend to question how close we meanwhile came to the initial promise – the use of tastants as medicines. Recent findings: Although the enormous complexity and experimental variability of studies investigating the effects of tastants on physiological functions still has not revealed a common fundament from which subsequent therapeutic measures could be designed, more and more evidence is mounting on an involvement of taste receptors and taste signaling molecules in the maintenance and fine regulation of gastrointestinal functions and immunity. Summary: Although the initial goal – using tastants to treat metabolic disorders – has, by far, not been reached, numerous promising findings suggest that dietary interventions could be devised to support conventional therapies in the future.